Tools and Biomechanical Modeling Use in Legal Disputes: Some Case Studies - Durante, Francesco (Frontiers in Bioengineering and Biotechnology, 2019)
The paper presents some of the biomechanical tools available for the forensic bioengineering expert. The tools range from the simple three-dimensional modeling environment to represent the geometries up to the analytical models based on the free-body diagram up to the multibody numerical models of rigid bodies. Through these tools the Forensic bioengineering expert is able to solve complex problems by providing quantitative results based on a scientific approach. In the work three case studies are presented concerning as many real cases, treated in court, of accidents in different contexts. The first relates to an accident in a filament factory where a worker remained with her body stuck in the production line, the second the investment of a pedestrian, and the last concerning the fall of a worker from a wall in a construction site. It has been shown that the approach to modeling may not always be necessarily complex. The first case, in fact, it was possible to solve with a simple three-dimensional geometric model that clearly highlighted the development of the facts, in the second case it was possible to set up a simple analytical model based on a free body diagram to search for the relationship between the forces developed on the invested leg demonstrating the relationship between the accident and the injuries reported. The third case, with the need for more complex modeling, was instead treated with a kinematic and dynamic multibody model that allowed, starting from the final position in which the victim was found, to trace the dynamics of the accident. In each case, the competence of the forensic bioengineering expert was crucial in identifying the correct modeling for the case in question with the choice of right data in order to arrive at reliable quantitative results.